Discovery of Furanoquinone Derivatives as a Novel Class of DNA Polymerase and Gyrase Inhibitors for MRSA Eradication in Cutaneous Infection - Yang, Shih-Chun; Tang, Kai-Wei; Lin, Chih-Hung; Alalaiwe, Ahmed; Tseng, Chih-Hua; Fang, Jia-You (Frontiers in Microbiology, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) is the primary microbe responsible for skin infections that are particularly difficult to eradicate. This study sought to inhibit planktonic and biofilm MRSA using furanoquinone-derived compounds containing imine moiety. A total of 19 furanoquinone analogs were designed, synthesized, and assessed for anti-MRSA potency. Among 19 compounds, (Z)-4-(hydroxyimino)naphtho[1,2-b]furan-5(4H)-one (HNF) and (Z)-4-(acetoxyimino)naphtho[1,2-b]furan-5(4H)-one (ANF) showed antibacterial activity superior to the others based on an agar diffusion assay. HNF and ANF exerted a bactericidal effect with a minimum inhibitory concentration (MIC) of 9.7~19.5 and 2.4~9.7 μg/ml, respectively. Both compounds were able to reduce the MRSA count by 1000-fold in biofilm as compared to the control. In vivo efficacy was evaluated using a mouse model of skin infection. Topical application of lead compounds significantly suppressed abscess occurrence and the MRSA burden, and also ameliorated the skin-barrier function. The biochemical assay indicated the compounds’ inhibition of DNA polymerase and gyrase. In silico docking revealed a favorable interaction of the compounds with DNA polymerase and gyrase although the binding was not very strong. The total DNA analysis and proteomic data suggested a greater impairment of some proteins by HNF than ANF. In general, HNF and ANF were similarly potent in MRSA inhibition in vitro and in vivo. The findings demonstrated that there was room for structural modification of furanoquinone compounds that could be used to identify anti-MRSA agent candidates.